A review on technologies and their usage in solid waste monitoring and management systems: Issues and challenges. (September 2015) - Hannan, M.A.; Abdulla Al Mamun, Md.; Hussain, Aini; Basri, Hassan; Begum, R.A.
Highlights: Classification of available technologies for SWM system in four core category. Organization of technology based SWM systems in three main groups. Summary of SWM systems with target application, methodology and functional domain. Issues and challenges are highlighted for further design of a sustainable system. Abstract: In the backdrop of prompt advancement, information and communication technology (ICT) has become an inevitable part to plan and design of modern solid waste management (SWM) systems. This study presents a critical review of the existing ICTs and their usage in SWM systems to unfold the issues and challenges towards using integrated technologies based system. To plan, monitor, collect and manage solid waste, the ICTs are divided into four categories such as spatial technologies, identification technologies, data acquisition technologies and data communication technologies. The ICT based SWM systems classified in this paper are based on the first three technologies while the forth one is employed by almost every systems. This review may guide the reader about the basics of available ICTs and their application in SWM to facilitate the search for planning and design of a sustainable new system.